2003
DOI: 10.1160/th03-02-0069
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 localization in carotid atherosclerotic plaques: correlation with clinical parameters

Abstract: Emerging evidence supports a role for platelets in the progression of atherosclerosis in addition to an involvement in thrombotic vascular occlusion. Platelet Factor 4 (PF4), a chemokine released by activated platelets, stimulates several pro-atherogenic processes. Therefore, we examined the localization of PF4 and the homologous protein, Neutrophil Activating Protein-2 (NAP-2) in lesions representing the evolution of human atherosclerotic plaques. Carotid plaques from 132 patients with critical carotid stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 24 publications
(22 reference statements)
6
137
0
2
Order By: Relevance
“…PF4 directly contributes to proatherogenic actions by promoting retention of lipoproteins (12). PF4 also interacts directly with oxidised low-density lipoprotein (oxLDL) leading to an induction of endothelial cell activation and dysfunction, macrophage foam cell formation, and VSMC migration and proliferation (13). Vascular wall cells express several SRs on their surface that mediate cellular effects of oxLDL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PF4 directly contributes to proatherogenic actions by promoting retention of lipoproteins (12). PF4 also interacts directly with oxidised low-density lipoprotein (oxLDL) leading to an induction of endothelial cell activation and dysfunction, macrophage foam cell formation, and VSMC migration and proliferation (13). Vascular wall cells express several SRs on their surface that mediate cellular effects of oxLDL.…”
mentioning
confidence: 99%
“…Macrophages internalise apoptotic cell fragments, bacterial endotoxins, and oxLDL, leading to lipid accumulation and foam cell formation. Interestingly, PF4 in macrophages correlates with the presence and the extension of atherosclerotic lesions (13,14). CD40 ligand (CD40L, CD154) and its receptor CD40 are costimulatory molecules of the tumour necrosis factor (TNF) and TNF receptor family.…”
mentioning
confidence: 99%
“…Pitsilos et al detected PF4 in the cytoplasm of luminal and neovascular endothelium, in macrophages and in regions of plaque calcification. The presence of PF4 in macrophages and neovascular endothelium significantly correlated with lesion grade (52). Furthermore, in a recent study, Yu et al demonstrated that E-selectin, an adhesion molecule involved in atherogenesis, is up-regulated in human umbilical vein endothelial cells exposed to PF4 (53).…”
Section: Sdf-1 and Pf4mentioning
confidence: 95%
“…In histopathological study on human carotid atherosclerotic, PF-4 accumulates within macrophages of the plaque in the early lesion and continues to accumulate in foam cells and neovascular endothelial cells as lesion progressed (Pitsilos et al, 2003). PF-4 is deposited on the endothelial cell surface and retained by subendothelial proteoglycan (Aidoudi & Bikfalvi, 2010).…”
Section: Tight Adhesion Of Platelet To Endothelial Cell Surfacementioning
confidence: 99%